What to expect from US economic policy after the presidential election - Anders Åslund (EconPol Forum, 2024)
Both candidates, Kamala Harris and Donald Trump, favor protectionism, but Trump to an extreme degree. The joint protectionism is mainly directed against Chinese technology. Trump favors mass deportation of immigrants, while the Democrats want orderly immigration. Nobody cares much about the unsustainable public finances, but the Republicans want to cut taxes, while the Democrats want to raise them for corporations and the wealthy. The rhetorical differences over green energy are largely fictive.
Keywords: 330